Significant variations in preoperative fluid resuscitation volumes delivered to elderly hip fracture patients at six level 1 trauma centers: an observational descriptive study. Issue 1 (3rd March 2022) - Willis, Jordan; Pelzl, Casey E.; Jarvis, Stephanie; Berg, Gina; Corrigan, Chad; Madayag, Robert; Reynolds, Cassandra; Tanner, Allen; Marshall, Gary; Lieser, Mark; Bar-Or, David
Abstract : Supplemental Digital Content is available in the text Abstract: Objective: To describe the variations in administration of preoperative (preop) fluids and in the volumes of fluid administered among geriatric hip fracture patients requiring surgical repair. Design: Observational descriptive. Setting: Six Level 1 trauma centers. Patients: A total of 595 patients aged ≥65 with ICD-10 codes indicating hip fracture and surgical repair were identified. Of these, 87.9% (n = 525) received preop fluid. The median volume of preop fluid delivered was 1500 mL (IQR: 1000–2250 mL). Intervention: None. Main Outcome Measures: Receipt of preop fluids; median volume of fluid received. Results: Receipt of preop fluid was significantly different by inter-hospital transfer, facility, BMI, hospital length of stay, and postop fluid volume. Age, sex, time to surgery, time to ambulation, and hospital disposition were not associated with preop fluid. There were significant differences in median preop fluid volumes by facility and postop fluid volume. Conclusion: This descriptive study of current practices among geriatric trauma patients with isolated hip fractures revealed significant differences in the use of preop fluid resuscitation and the resuscitation volumes administered. Treating facility may be the most substantial source of variation highlighting the need for a guideline on fluid resuscitation. These observed variations may be a result of patient characteristics or provider discretion and should be evaluated further.